Level of Phosphate, Nitrate and Dissolved Oxygen in Talise Island Waters, North Sulawesi - Simon I Patty (Jurnal Ilmiah PLATAX, 2013)
Phosphate and nitrate are a source of food for micro-organisms, while dissolved oxygen is required in the process of respiration in variety of aquatic organisms. Observations of phosphate, nitrate and dissolved oxygen levels have been conducted in the waters of Talise Island, North Sulawesi. Phosphate and nitrate concentration measurements carried out using spectrophotometric method, while dissolved oxygen was determined by electrochemical methods. Overall observations of phosphate, nitrate and dissolved oxygen levels in Talise Island waters, ranging between 0.005 to 0.056 mg/l, 0.012 to 0.034 mg/l and 5.05 to 6.01 ppm, respectively. Levels of phosphate, nitrate and dissolved oxygen in Talise Island Waters were still considered normal and suitable for marine life.Keywords : Phosphate, nitrate, dissolved oxygen,Talise Island, North Sulawesi